Analisis Strategi Pemasaran Produk Pizza Pada Home Industri Azzea Kitchen Di Kelurahan Margodadi Metro Selatan - Anggun Yunita Putri; Yateno; Ana Septiani (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze the internal and external factors that affect Azzea Kitchen Home Industry and analyze internal and external marketing strategies to improve market competitiveness. The research method used is qualitative with data collection through interviews, observation, documentation, and data analysis. The analysis was conducted using the SWOT method, which resulted in 6 strengths, 4 weaknesses, 3 opportunities, and 2 threats. From the results of weighting, rating, and scores with IFAS and EFAS, it can be seen that the Azzea Kitchen Home Industry is in quadrant I, indicating a support strategy for growth oriented towards aggressive strategies. This strategy aims to optimally utilize the company's strengths, cooperating with existing opportunities, otherwise known as the SO strategy. Focusing on marketing strategies, Azzea Kitchen Home Industry can implement an aggressive approach by utilizing business capital efficiently during holidays and national holidays to increase sales and brand image. Maximize production capacity during the holiday season, and take advantage of easily available raw materials. Furthermore, strengthen the presence of online consumers through product innovation and improving the quality of appealing flavors. Technology can also be utilized for aggressive marketing strategies, strengthening market share and increasing competitiveness in a competitive market. Thus, the implementation of this strategy is expected to have a positive impact on the Market